I01 QRX-704, a novel antisense oligonucleotide therapy, designed to prevent hd pathology while maintaining htt function. (September 2018) - Klein, Pontus; Karneva, Zhana; Toonen, Lodewijk; Kim, Hyeongju; Caron, Nicholas; Graaf, Linda van der; Buil, Levi; Horst, Geert van der; Anthonijsz, Herma; Ham, Frits van der; Beumer, Wouter; Hayden, Michael; et al.
Abstract : Background: QRX-704 is a novel antisense oligonucleotide-based therapeutic approach, aiming to mitigate mutant Huntingtin (mHTT) toxicity, while maintaining physiological HTT function. Proteolytic cleavage of mHTT generates toxic N-terminal fragments that are hypothesized to be the main contributor to the pathogenesis of Huntington disease (HD). These fragments are formed from a cascade of proteolytic cleavages, initiated by caspase-6 cleavage at position D586. Importantly, HTT586 cleavage is required for HD-like phenotypes in the YAC128 mouse model. Moreover, mHTT cleavage in turn increases caspase-6 activity, driving pathology in a toxic forward-feedback loop. While toxicity stemming from mHTT cleavage is the primary pathogenic mechanism, data indicates that HTT loss-of-function exacerbates pathology. In addition, maintaining wild type HTT function may be critical for safety of HTT-targeted therapeutics when treating patients for a long period of time. Aims: QRX-704 functions at the pre-mRNA level by activating an alternative HTT splice-isoform (HTT Δ12), disrupting the critical HTT586 caspase-6 cleavage site, thus preventing formation of toxic N-terminal fragments. The aim of the study is to pharmacologically characterize QRX-704 for preclinical development, and describe the novel HTT Δ12 isoform. Methods/techniques: Biodistribution, tolerability, immunogenicity, and pharmacodynamic activity of QRX-704, administered by intracerebroventricular (ICV) injection was assessed in wild type and YAC128 mice. Biophysical and biochemical characterization of HTT Δ12 was performed using purified protein, with caspase-6 cleavage assays, CD-spectroscopy, and post-translational modification mapping. Results/outcome: ICV administration of QRX-704 was well tolerated and lead to efficient distribution and cellular uptake throughout the brain. QRX-704 induced formation of HTT Δ12 mRNA and protein in striatum and cortex in a dose-dependent manner. In vitro, recombinant HTT Δ12 is fully resistant to HTT586 caspase-6 cleavage and does not display major differences in biochemical and biophysical assays, compared to canonical HTT. Conclusions: QRX-704 constitutes a novel therapeutic approach to HD, potentially preventing toxicity of mHTT while maintaining HTT function.